PENERAPAN MEDIA CERITA BERGAMBAR UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV B SDN 39 PADANG KALUA - Muh. Wira Eko S; Wasilah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the improvement of learning outcomes in the Indonesian language subject of fairy tales. This study was conducted in class IV B of SD Negeri 39 Padang Kalua in the 2025 academic year consisting of 30 students. The data in this study were obtained through observation and tests. The data obtained were analyzed using quantitative descriptive. Improvement in learning outcomes of class IV B students of SD Negeri 39 Padang Kalua in learning Indonesian language material fairy tales through the application of illustrated story media. Cycle II The percentage of completion of fairy tale material using illustrated story media for class IV B students of SD Negeri 39 Padang Kalua in cycle II was 96.67% or 29 out of 30 students were included in the complete category according to the school's KKM, namely 69 then 3.33% or 1 out of 30 students were included in the incomplete category. The activity of student learning outcomes through the application of illustrated story media in learning Indonesian students of class IV B of SD Negeri 36 Padang Kalua resulted in changes in student behavior. This is evident in the student learning outcomes in cycle I, which reached 44.4% in the "fair" category, and increased to 100% in the "very good" category in cycle II.